EXCAVACIONES EN WAYCHAUPAMPA, POBLADO DEL PERÍODO FORMATIVO EN AYACUCHO - Pérez Calderón, Ismael (2017)
The purpose of the present investigation is to make known about emergency excavations in the archaeological settlement of Waychaupampa, Ayacucho, which led to the definition of remains of a settlement of the Formative period associated with architectural vestiges, lithic, bone and ceramics, the latter of several styles And artifacts of pottery production indicators of various reoccupations and production of pottery from at least the Middle Formative (900-500 BC), time attributed to the construction of a “D” enclosure, 1000 years later, outside Taken as a model by architects and builders Wari.